Ulnar-sided wrist pain in the athlete - Dineen, H. A.; Greenberg, J. A. (Clinics in Sports Medicine, 2020)
Ulnar-sided wrist pain is a common problem in athletes that can be challenging owing to its frequent combination of overuse in conjunction with acute injury. Repetitive pronosupination, wrist flexion and extension, as well as radial and ulnar deviation can predispose the athlete to injury of ulnar structures. Careful understanding of the sport-specific injuries as well as the underlying biomechanics are key to understanding and treating the athlete. In this article, we discuss the most frequent causes of ulnar-sided wrist pain in the athlete and focus on anatomy and pathophysiology, presentation, and diagnosis, as well as nonoperative and operative treatment options.